Exploring the Dutch Bruynzeel Kitchen Through the Negotiations of Its Two Designers, Limperg and Zwart - Geerinkcx, Selin; De Vos, Els (UI Scholars Hub, 2024)
During the interwar period, numerous endeavours were made to develop a rational kitchen, also called a laboratory kitchen, namely one that prioritised labour-saving efficiency through thoughtful layout and design. Catherine Beecher's work is often credited as its starting point. By synthesising household reformers' experiences and architects’ design expertise, scholars have extensively examined how rational kitchens evolved. This paper discusses the conception of the standardised Dutch Bruynzeel Kitchen (1938) by the collaborative efforts of two designers with distinct yet complementary interior design profiles. Renowned Dutch designer Piet Zwart, widely recognised for his contributions, finalised the technical drawings and promotional materials for this iconic kitchen. Less acknowledged is the early involvement of Dutch architect Koen Limperg, son of a business economics professor, who drew the preliminary designs. Interestingly, this kitchen design was developed while body culture emerged in the Netherlands. Complementing already existing research from art history, anthropology, the history of technology, and gender studies, this paper, based on literature and archive research, investigates through an interior design lens how both designers integrated their respective practices and expertise into the Bruynzeel Kitchen's design, incorporating elements of physical activities (dance, gym, sports) and household economics.